Heart rate variability may index emotion dysregulation in alcohol-related intimate partner violence - Fink, Brandi C.; Claus, Eric D.; Cavanagh, James F.; Hamilton, Derek A.; Biesen, Judith N. (Frontiers in Psychiatry, 2023)
Introduction Intimate partner violence is a serious public health problem that costs the United States more than 4.1 billion in direct medical and mental health costs alone. Furthermore, alcohol use contributes to more frequent and more severe intimate partner violence incidents. Compounding this problem is treatments for intimate partner violence have largely been socially informed and demonstrate poor efficacy. We argue that improvements in intimate partner treatment will be gained through systematic scientific study of mechanisms through which alcohol is related to intimate partner violence. We hypothesize that poor emotional and behavioral regulation as indexed by the respiratory sinus arrythymia measure of heart rate variability is a key mechanism between alcohol use and intimate partner violence. Method The present study is a placebo-controlled alcohol administration study with an emotion-regulation task that investigated heart rate variability in distressed violent and distressed nonviolent partners. Results We found a main effect for alcohol on heart rate variability. We also found a four-way interaction whereby distressed violent partners exhibited significant reductions in heart rate variability when acutely intoxicated and attempting to not respond to their partners evocative stimuli. Discussion These findings suggest that distressed violent partners may adopt maladaptive emotion regulation strategies such as rumination and suppression when intoxicated and attempting to not respond to partner conflict. Such strategies of emotion regulation have been shown to have many deleterious emotional, cognitive and social consequences for individuals who adopt them, possibly including intimate partner violence. These findings also highlight an important novel treatment target for intimate partner violence and suggest that novel treatments should focus on teaching effective conflict resolution and emotion-regulation strategies that may be augmented by biobehavioral treatments such as heart rate variability biofeedback.